Avoiding Emotional Bonds: An Examination of the Dimensions of Therapeutic Alliance Among Cannabis Users - Healey, Alison; Kay-Lambkin, Frances; Bowman, Jenny; Childs, Steven (Frontiers in Psychiatry, 2013)
There is a growing need to provide treatment for cannabis users, yet engaging and maintaining this population in treatment is particularly difficult. Although past research has focused on the importance of therapeutic alliance on drug treatment outcomes, this is the first study to examine the dimensions of therapeutic alliance for cannabis users compared with users of alcohol or other drugs in a naturalistic setting. The acceptability of Internet-delivered interventions for drug and alcohol treatments is also investigated. Participants (N = 77) included clients who were receiving outpatient drug and alcohol treatment at a publicly-funded health service, including a Specialist Cannabis Clinic. The results indicated that one particular domain of alliance, Bond, was consistently lower, from both client and clinician perspectives, for current cannabis users relative to those not currently using cannabis. Client perceptions of Bond decreased as the severity of cannabis use increased (r =-0.373, p=0.02). Cannabis Clinic clients did not report a significantly lower Bond with their clinicians, suggesting that specialised cannabis services may be better placed to provide appropriate treatment for this population than embedding cannabis treatment within traditional drug and alcohol treatment teams. In addition, Internet/computer based treatments may be one potential way to engage, transition or retain cannabis users in treatment. Trial Registration: Australian Clinical Trial Registration Number: ACTRN12611000382976